Experimental reconstruction of double‐stranded break repair‐mediated plastid DNA insertion into the tobacco nucleus. (16th December 2017) - Wang, Dong; Gu, Jinbao; David, Rakesh; Wang, Zhen; Yang, Songtao; Searle, Iain R.; Zhu, Jian‐Kang; Timmis, Jeremy N.
Summary: The mitochondria and plastids of eukaryotic cells evolved from endosymbiotic prokaryotes. DNA from the endosymbionts has bombarded nuclei since the ancestral prokaryotes were engulfed by a precursor of the nucleated eukaryotic host. An experimental confirmation regarding the molecular mechanisms responsible for organelle DNA incorporation into nuclei has not been performed until the present analysis. Here we introduced double‐stranded DNA breaks into the nuclear genome of tobacco through inducible expression of I‐ Sce I, and showed experimentally that tobacco chloroplast DNAs insert into nuclear genomes through double‐stranded DNA break repair. Microhomology‐mediated linking of disparate segments of chloroplast DNA occurs frequently during healing of induced nuclear double‐stranded breaks (DSB) but the resulting nuclear integrants are often immediately unstable. Non‐Mendelian inheritance of a selectable marker ( neo ), used to identify plastid DNA transfer, was observed in the progeny of about 50% of lines emerging from the screen. The instability of these de novo nu clear insertions of p last id DNA ( nupt s) was shown to be associated with deletion not only of the nupt itself but also of flanking nuclear DNA within one generation of transfer. This deletion of pre‐existing nuclear DNA suggests that the genetic impact of organellar DNA transfer to the nucleus is potentially far greater than previously thought. Significance Statement: Chloroplast DNA tracts insert into the nuclear genome during DSB repair. Most of the integrants are unstable as a result of rapid deletion of the insert itself and of native nuclear flanking DNA. The insertion and the subsequent deletion processes are likely to have profound evolutionary consequences.